Optimal welfare price for a road corridor with heterogeneous users - Ortega Hortelano, Alejandro; Vassallo, Jose Manuel; Pérez, Juan Ignacio (Transport, 2019)
In some countries it is fairly common to see two roads with the same origin and destination competing in the same corridor. One of them is usually a toll highway that offers a better quality to the users compared to its alternative: a free parallel single road, which might be tolled as well. This kind of transport network has been largely studied in the academic literature and particularly the optimal combination of tolls that maximizes economic efficiency. If both roads are tolled the problem is known as the first best, otherwise it is called the “untolled alternative”. There is a gap regarding how income distribution affects the optimal toll. The main objective of this paper is to add knowledge in the area by analysing the influence of the distribution of the Values of Travel Time (VTT) of the users of this corridor on the optimal combination of tolls. To solve this problem, the authors define a mathematical model aimed at obtaining the optimal welfare price for this kind of corridor under the hypothesis that drivers decide over the expectation of free flow conditions. The results show that the higher the average VTT the higher the optimal price, and the higher the dispersion (variance) of this VTT the lower the optimal price. It was also found that low income users who are not able to internalize externalities should not travel. Finally, first best pricing and untolled alternative schemes match for high income users.